Local Government Debt and Managerial Incentives: Evidence from China - Song, Zirui (International Journal of Global Economics and Management, 2024)
This study investigates the impact of local government debt on managerial incentives. The results show a significant negative relationship between local government debt and managerial incentives. The effect is more pronounced for equity-based incentives in non-state-owned enterprises and for salary-based incentives in state-owned enterprises. Furthermore, we address potential endogeneity concerns by employing an instrumental variable (IV) approach. Our findings underscore the need for adaptive compensation strategies to mitigate the risks associated with fiscal pressures.